Risky road behaviours cluster and share predictor variables with smoking and drinking, and anti-social behaviours during early adolescence. (March 2021) - Twisk, Divera; Senserrick, Teresa
Abstract: Context: The prime cause of death among young adolescents - 12 to 15 years of age - are unintentional injuries, especially injuries in traffic crashes. In the Netherlands, they lose their lives as pedestrians, cyclists or as passengers of young drivers. The age-related rise in deliberate risk-taking is one of the contributing factors. To date, widely implemented strategies that solely target risky road behaviour are only marginally effective. To date, an unexplored but promising approach for effective strategies is to explicitly address risk-taking tendency, since this may not only result in risky decisions in traffic but also in health and social position. Further, these risky decisions may share the same underlying contributors, such as sensitivity to peer pressure. To date, these presumed relationships have not yet been tested. Purpose: This study contributes to the developmental of prevention strategies, by testing that a) risky road behaviour cluster with other types of risk behaviours and (b) risk behaviours share the same underlying factors, such as developmental adolescent characteristics (CADs) and presence of risk behaviours in the perceived social environment (parents and peers). Methods: Surveys were completed in class in several schools by 417 students, 46% male, all in the first two years of secondary school in the Netherlands. Results: Correlations showed strong associations between risky road behaviour, smoking and/or drinking and anti-social behaviour, and weaker associations with a poor diet. These behaviours also shared predictor variables in regression modelling: peers acting risky and riding as passengers with dangerous driver s. Age and gender did not play a significant role. Implications and contributions: The effectiveness and efficiency of road safety programmes for young adolescents may benefit from an integrated rather than a silo approach, by addressing clusters of risk behaviours and the influence of underlying factors related to adolescent development and their social environment. Highlights: Young adolescents acting risky in traffic also more often smoke and misuse alcohol and behave anti-socially. These risk behaviours share similar predictors: having risky friends and parents, and been passengers of risky drivers. Peer pressure only shows in risky behaviour on the road in groups. Integrated Health monitors and interventions require identifying and targeting risk clusters and shared predictors. Understanding clusters of risk behaviour and its shared predictors contributes to effective interventions.